2017
DOI: 10.1038/emm.2017.173
|View full text |Cite
|
Sign up to set email alerts
|

Lower serum extracellular superoxide dismutase levels are associated with polyneuropathy in recent-onset diabetes

Abstract: Increased oxidative stress is implicated in the pathogenesis of experimental diabetic neuropathy, but translational evidence in recent-onset diabetes is scarce. We aimed to determine whether markers of systemic oxidative stress are associated with diabetic sensorimotor polyneuropathy (DSPN) in recent-onset diabetes. In this cross-sectional study, we measured serum concentrations of extracellular superoxide dismutase (SOD3), thiobarbituric acid reactive substances (TBARS), and reduced glutathione (GSH) in 107 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 26 publications
1
28
1
1
Order By: Relevance
“…The discrepancy between the first of the aforementioned studies and our study cannot be explained by technical factors, as both studies used the same assay for quantification of SOD3 and also similar preanalytical procedures. However, the other study was based on a much younger study sample and lacked a population‐based design, so that selection bias cannot be excluded.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…The discrepancy between the first of the aforementioned studies and our study cannot be explained by technical factors, as both studies used the same assay for quantification of SOD3 and also similar preanalytical procedures. However, the other study was based on a much younger study sample and lacked a population‐based design, so that selection bias cannot be excluded.…”
Section: Discussioncontrasting
confidence: 64%
“…Based on 2 previous observations, we had expected associations in the opposite direction. The first study found that SOD3 levels were lower in individuals with recent‐onset type 2 diabetes compared with nondiabetic individuals and in diabetes patients with DSPN compared with DSPN‐free diabetes patients . The second study reported that gene variants that were linked to higher SOD3 levels had a protective effect on the risk for cardiovascular events in patients with diabetes .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact pathogenesis is complex and oxidative stress has a significant role in the pathogenesis of DN and its progression to ESRD. In recent years, a variety of biomarkers of oxidative stress associated with DN has been found and the most important ones used in clinical studies are presented ( Table 2 ) [ 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 ].…”
Section: Biomarkers Of Oxidative Stress In Development and Progresmentioning
confidence: 99%